2023
DOI: 10.1021/acs.macromol.2c01565
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Structure and Rheological Properties of Polyelectrolyte-Based Hydrogels through Counterion-Specific Effects

Abstract: Tuning at will the properties of gel-forming systems is of key relevance for many biotechnological, agricultural, and biomedical applications. For polyelectrolyte-based gels, ion-specific effects can be an attractive way for this purpose. This study investigates the counterion-specific effect on the microscopic structure and the rheological properties of a physical hydrogel formed of ionene-type cationic polyelectrolytes. The focus is on two monovalent halide counterions (F– and Cl–) and a divalent counterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This hydrogel is formed from cationic polyelectrolytes based on ionenes, a class of polyelectrolytes containing quaternary ammonium parts in the main chain [8,9,10]. Additionally, the presence in the main chain of aromatic rings and amide moities allows gelation through a combination of electrostatic repulsions, π-π stacking, hydrogen bonding and anion-π and cation-π interactions that can be tune according to the nature and the valence of the couterions [11]. In a previous study, we investigated the organisation of clay nanoplatelets in this 25 ionene-based hydrogel [10].…”
Section: Introductionmentioning
confidence: 99%
“…This hydrogel is formed from cationic polyelectrolytes based on ionenes, a class of polyelectrolytes containing quaternary ammonium parts in the main chain [8,9,10]. Additionally, the presence in the main chain of aromatic rings and amide moities allows gelation through a combination of electrostatic repulsions, π-π stacking, hydrogen bonding and anion-π and cation-π interactions that can be tune according to the nature and the valence of the couterions [11]. In a previous study, we investigated the organisation of clay nanoplatelets in this 25 ionene-based hydrogel [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that ion-specific effects manifest themselves more strongly for anions than cations [28,29]. Solutions and gels based on cationic chains with compensating anions, such as ionenes [20,21,30], show indeed stronger ion specific effects than anionic PEs, such as the widely studied polystyrene sulfonate [16,[31][32][33][34]. Needless to say, any purely electrostatic theory, such as the scaling-approach of de Gennes, Manning theory of counterion condensation [35,36] or indeed the Poisson-Boltzmann approach [32] cannot account for these effects, as hydration properties of solvated ions do not come into consideration.…”
Section: Introductionmentioning
confidence: 99%